Optimization of ion-optics system for x-ray quasi-monochromatic source on the basis of electrostatic accelerator - S. O. Vershynskyi; O. G. Ponomarev; V. Yu. Storizhko; V. L. Denysenko; M. V. Iljashenko (Ядерна фізика та енергетика)
Ion-optics system with two doublets of electrostatic quadrupole lenses for X-ray quasimonochromatic source was selected. Two variants of lens excitation for stigmatic focusing with two and four independent power supplies are considered. It is shown that using of four independent power supplies leads to improvement of focused ion beam parameters at converter.